2011
DOI: 10.1097/wnr.0b013e328344a666
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9 promotes differentiation of mouse bone mesenchymal stem cells into neurons by Notch signaling

Abstract: MicroRNAs are members of the family of noncoding small RNAs that regulate gene expression either by inhibiting mRNA translation or by promoting mRNA degradation at the posttranscriptional level. They play an important role in the differentiation of bone marrow-derived mesenchymal stem cells (MSCs) into neurons. However, the role of microRNAs in this process remains to be poorly understood. Studies have shown that Notch signaling is involved in regulating MSC differentiation. Here, we found that microRNA-9 coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…After one by one attempts, we established the novel induction system to derive neuronal cells from MSCs. In contrast, recent studies have shown that Notch signaling inhibits the differentiation of BMSCs into neurons (Yanjie et al 2007;Jing et al 2011). In addition, Notch signaling has been shown to promote the self-renewal of and to inhibit the differentiation of NSCs into a more mature state.…”
Section: Recovery From Stroke By Grafting Neurosphere-like Spheres Dementioning
confidence: 86%
See 1 more Smart Citation
“…After one by one attempts, we established the novel induction system to derive neuronal cells from MSCs. In contrast, recent studies have shown that Notch signaling inhibits the differentiation of BMSCs into neurons (Yanjie et al 2007;Jing et al 2011). In addition, Notch signaling has been shown to promote the self-renewal of and to inhibit the differentiation of NSCs into a more mature state.…”
Section: Recovery From Stroke By Grafting Neurosphere-like Spheres Dementioning
confidence: 86%
“…They also reported that Tuj-1-positive cells, with a monopolar or bipolar morphology, occasionally emerged after the introduction of Mash1, and that no other factor by itself, other than Mash1, could induce these types of neuron-like cells. As mentioned, recent studies have revealed that the inhibition of the Notch signaling pathway can promote the expression of neuronal genes in BMSCs, in which Mash1 might be expressed, because the expression of the NICD gene was inhibited, indicating the down-regulation of Hes1 and Hes5, the negative regulators of the Mash1 gene (Yanjie et al 2007;Jing et al 2011). Yanjie et al (2007 also demonstrated that 30% of the Notch-1-shRNA-transfected cells died by apoptosis.…”
Section: Stemness Of Mscs and Discovery Of A Novel Stem Cell Populatimentioning
confidence: 93%
“…miRNAs may facilitate the differentiation of bone-marrow-derived stromal cells into neurons via Notch regulation. Jing et al 91 reported that miR-9 facilitates the differentiation of bone-marrow-derived mesenchymal stem cells (MSCs) into neurons via Notch-1 repression, implying the possibility of developing a promising approach using an miRNA-based cocktail to induce stem cell differentiation into neurons. Furthermore, miR-34a has been reported to downregulate Notch-1and Notch-2 protein expression in glioma stem cells via targeting DLL1, and Notch-1 and Notch-2 3 0 UTR, 92,93 Expression of miR-34 can inhibit cell invasion.…”
Section: B Micrornas Control Neuronal Progenitor Proliferation and Dmentioning
confidence: 99%
“…Other methods to induce MSCs into cells with neural characteristics include: transfection of MSCs with Noggin and Notch transcription factors (Dezawa et al, 2004;Kohyama et al, 2001); manipulation with surface proteins of culture substrate (Qian & Saltzman, 2004); co-culturing MSCs with NSCs or neural cells (Alexanian, 2005;Chu, Yu, Zhang, & Yu, 2008;Krampera et al, 2007;Wislet-Gendebien et al, 2005;Y. Q. Zhang et al, 2010); and growing MSCs as spheres in cultures (Shiota et al, 2007), transfection of MSCs with microRNA-9 (Jing et al, 2011). In several other studies, MSCs were turned into multipotent stage and then induced into neural cell lineages, by exposing them to appropriate neural differentiation conditions (Alexanian, 2007;Kohyama et al, 2001;Qu et al, 2004).…”
Section: In Vitro Neural Differentiation Potential Of Mscsmentioning
confidence: 99%